PELAKSANAAN TUGAS KEPALA DESA DALAM MENDUKUNG PERKEMBANGAN PARIWISATA PANTAI SOLOP DI KECAMATAN MANDAH KABUPATEN INDRAGIRI HILIR TAHUN 2015-2016 - Syukri, Mohd.; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Implementation of the Task of the Village Head in supporting the development of Solop Beach tourism as contained in Law No. 6 of 2014 concerning Villages, in Article 16 Points o which states that the Village Head is obliged to develop the potential of natural resources and preserve the environment. As for the Problem Formulation in this study, namely: First, How the Implementation of Village Heads' Duties in Supporting the Development of Solop Beach Tourism in Mandah Subdistrict, Indragiri Hilir Regency Year 2015-2016, What are the obstacles to Pulau Cawan Village Chief in Supporting the Development of Solop Beach Tourism In Mandah District, Indragiri Hilir Regency, 2015-2016. As for the purpose of this thesis, namely: First, To Know the Role of Pulau Cawan Village Chief in improving the Development of Solop Beach Tourism. Second, To Know the obstacles of Cawan Island Village Chief in Increasing Solop Beach Tourism. This research is a qualitative research. This research was conducted in Pulau Cawan Village, Mandah District, Indragiri Hilir Regency. The techniques used to collect data in this study are (1) Interviews, (2) Observations, and (3) Documentation. The conclusion of this study shows that the Implementation of the Task of the Village Chief in supporting tourism development in Solop Beach is still not running effectively, such as garbage on the shores of Solop Beach, and there are no means of transportation and damaged buildings for visitors and tourists, resulting in lost tourism objects. for its beauty, the author gives advice There should be an active role of the Government which is represented by the Village Head and related parties to pay more attention to Solop Beach tourism objects in improving tourism development in Solop Beach. Key Words: Implementation, Village Head, Development of Tourism.